EFFECT OF ACIDIC ON THE PHYSICOCHEMICAL PROPERTIES AND COLLAPSE POTENTIAL OF GYPSEOUS SOILS: EXPERIMENTAL INVESTIGATIONS - Falah Hassan Rahil,; Ahmed Sameer Abdulrasool,; Husam Hikmat Baqir,; Saad Faik Abbas Al-Wakel, (GEOMATE Journal, 2023)
The gypseous soils present a challenge when utilizing them as a foundation for structures, making them a problematic soil type. However, when gypseous soils are saturated by anticipated sources such as acidic results from sewerage of industry, the minerals are soluble, resulting in the subsidence of the structures. The study aims to provide valuable insights into the behavior of gypseous soils, which are known for their tendency to collapse and settle. It considered the impact of acidity on the potential for the collapse of gypseous soils, a crucial area of research that can benefit multiple fields. To comprehend the mechanisms governing the behavior of acidic gypseous soils, an investigation in the lab is carried out to determine how the presence of acidity in varying concentrations affects the possibility of the collapse of gypsum soils. To examine the impact of acidity on the chemical composition of gypseous soils, a Scanning Electron Microscope (SEM) analysis was conducted. The results of the analysis were used to create a map of this effect. In addition, the effect of different parameters such as unit weight and initial water content of gypseous soils and their effect on the collapse potential is studied. The results indicate that gypsum dissolves due to a change in the chemical composition of the soil, resulting in an increase in the collapse potential of gypseous soils. Consequently, the concepts of gypsum soil treatment must take into consideration the nature of the facilities constructed on this type of soil, such as industrial structures.